2001
DOI: 10.1007/s002030000246
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus nidulans homoaconitase gene lysF is negatively regulated by the multimeric CCAAT-binding complex AnCF and positively regulated by GATA sites

Abstract: In beta-lactam-antibiotic-producing fungi, such as Aspergillus (Emericella) nidulans, L-alpha-aminoadipic acid is the branching point of the lysine and penicillin biosynthesis pathways. To obtain a deeper insight into the regulation of lysine biosynthesis genes, the regulation of the A. nidulans lysF gene, which encodes homoaconitase, was studied. Band-shift assays indicated that the A. nidulans multimeric CCAAT-binding complex AnCF binds to two of four CCAAT motifs present in the lysF promoter region. AnCF co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…On the other hand, CCAAT boxes in filamentous fungi showing repressing functions (e.g. the lysF promoter [A. nidulans] and the xyn2 promoter [H. jecorina]) have also been observed (Weidner et al 2001;Würleitner et al 2003). The induction-specific complex is counteracted by an uncharacterised DNAbinding protein (complex) binding to a 5′-AGAA-3′ box immediately upstream of the XAE (Stricker et al, manuscript in preparation).…”
Section: Interplay Of Xyr1 With Specific Transcriptional Regulators Amentioning
confidence: 99%
“…On the other hand, CCAAT boxes in filamentous fungi showing repressing functions (e.g. the lysF promoter [A. nidulans] and the xyn2 promoter [H. jecorina]) have also been observed (Weidner et al 2001;Würleitner et al 2003). The induction-specific complex is counteracted by an uncharacterised DNAbinding protein (complex) binding to a 5′-AGAA-3′ box immediately upstream of the XAE (Stricker et al, manuscript in preparation).…”
Section: Interplay Of Xyr1 With Specific Transcriptional Regulators Amentioning
confidence: 99%
“…However, in the xyn2 promoter, a similar mutation in the CCAAT-box of XAE resulted in a small but reproducible increase both in basal and in induced xyn2 gene transcription, indicating that the Hap2/3/5 complex partially mediates xyn2 repression. Negative regulation by the human Hap homologue NF-Y has been observed in some cases (e.g., topoisomerase II␣, the type II transforming growth factor ␤ receptor, and the varicella-zoster virus ORF62 [12,13,21]) and, more recently, also for the lysF promoter of the fungus A. nidulans (37). In hematopoietic cells, repression of the proteintyrosine phosphatase gene by NF-Y was shown to be dependent on its interaction with the histones (40).…”
mentioning
confidence: 99%
“…Remarkably, the promoter region of lysF contains several GATA motifs which potentially represent SREA binding sites. But since mutational analysis showed that at least two of these GATA sites mediate a positive effect on lysF expression, a direct involvement of the repressor SREA seems to be doubtful (31).…”
mentioning
confidence: 99%